Depression and incident cardiovascular disease - El-Battrawy, Ibrahim; Behnes, Michael; Akın, Ibrahim (The journal of the American Medical Association, 2021)
To the Editor In their recent pooled analysis from 563255 participants in 22 prospective cohorts, Dr Harshfield and colleagues demonstrated that depressive symptoms reported at baseline were associated with cardiovascular disease (CVD) incidence. It appears that there are several limitations to this study. First, the definition of fatal and nonfatal coronary heart disease was not well defined.Second, it is important to highlight that takotsubo syndrome (TTS) may mimic acute coronary syndrome and fatal coronary artery disease, presenting with similar clinical symptoms, electrocardiographic changes, and elevated cardiac biomarkers. In addition, emotional and physical events may trigger both of these cardiac conditions. It is therefore possible that some of the cases reported in this study were related to TTS. Of note, it has been reported that approximately 2% to 5% of patients with suspected acute coronary syndrome on the basis of coronary artery disease may have TTS. In addition, TTS may be underestimated. Notably, several complications of TTS, such as stroke and long-term mortality, are estimated to be similar or increased compared with acute coronary syndrome from coronary artery disease.
Gesehen am 18.06.2021